Radiographic features and poor prognostic factors of interstitial lung disease with nivolumab for non–small cell lung cancer. Issue 4 (24th February 2021) - Saito, Yoshinobu; Sasaki, Shinichi; Oikado, Katsunori; Tominaga, Junya; Sata, Masafumi; Sakai, Fumikazu; Kato, Terufumi; Iwasawa, Tae; Kenmotsu, Hirotsugu; Kusumoto, Masahiko; Baba, Tomohisa; Endo, Masahiro; et al.
Abstract: Nivolumab can cause interstitial lung disease (ILD), which may be fatal; however, mortality risk factors have not been identified. This postmarketing study evaluated the poor prognostic factors of ILD in nivolumab‐treated patients with non–small cell lung cancer (NSCLC) in Japan. Clinical and chest imaging findings for each ILD case were assessed by an expert central review committee, and prognosis was evaluated by radiographic findings, including the presence/absence of peritumoral ground‐glass opacity (peritumoral‐GGO). Poor prognostic factors were identified by univariate and multivariate Cox regression analysis. Of the 238 patients with nivolumab‐induced ILD, 37 died. The main radiographic patterns of ILD were cryptogenic organizing pneumonia/chronic eosinophilic pneumonia–like (53.4%), faint infiltration pattern/acute hypersensitivity pneumonia–like (20.2%), diffuse alveolar damage (DAD)‐like (10.9%), and nonspecific interstitial pneumonia–like (6.3%). The main poor prognostic factors identified were DAD‐like pattern (highest hazard ratio: 10.72), ≤60 days from the start of nivolumab treatment to the onset of ILD, pleural effusion before treatment, lesion distribution contralateral or bilateral to the tumor, and abnormal change in C‐reactive protein (CRP) levels. Of the 37 deaths due to ILD, 17 had DAD‐like radiographic pattern, three had peritumoral‐GGO, and five had a change in radiographic pattern from non‐DAD at the onset to DAD‐like. Patients with NSCLC who develop ILD during nivolumab treatment should be managed carefully if they have poor prognostic factors such as DAD‐like radiographic pattern, onset of ILD ≤60 days from nivolumab initiation, pleural effusion before nivolumab treatment, lesion distribution contralateral or bilateral to the tumor, and abnormal changes in CRP levels. Abstract : This postmarketing study showed that diffuse alveolar damage (DAD)‐like pattern, ≤60 days from the start of nivolumab treatment to the onset of interstitial lung disease (ILD), pleural effusion before treatment, lesion distribution contralateral or bilateral to the tumor, and abnormal change in C‐reactive protein levels were common poor prognostic factors of ILD in nivolumab‐treated patients with non–small cell lung cancer (NSCLC). Of the 37 deaths due to ILD, 17 had DAD‐like radiographic pattern, and five had a change in radiographic pattern from non‐DAD at the onset to DAD‐like. Patients with NSCLC who develop ILD during nivolumab treatment should be managed carefully if they have poor prognostic factors.